2018
DOI: 10.1002/pbc.27244
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in pediatric hematology/oncology—time to address the elephant by name

Abstract: The last decade has brought increasing recognition that the wellness of health care providers has an impact on the quality of care, patient satisfaction, and health care economics. This review will describe models of burnout, discuss the impact of burnout on medicine with a focus on pediatric hematologists/oncologists, and present interventions that may help ameliorate physician burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…The inherent emotional stress, compassion fatigue and burnout associated with the long-term exposure to the psychosocial ramifications of pediatric oncology care is well described in the literature. 6,8, 23,24,25 Professional development and continuing education opportunities are essential for maintaining skills, preventing burnout along and creating a culture that encourages self-care. Training opportunities are essential to introduce multidisciplinary psychosocial trainees to pediatric oncology and assure an ongoing pipeline of individuals for the future.…”
Section: Discussionmentioning
confidence: 99%
“…The inherent emotional stress, compassion fatigue and burnout associated with the long-term exposure to the psychosocial ramifications of pediatric oncology care is well described in the literature. 6,8, 23,24,25 Professional development and continuing education opportunities are essential for maintaining skills, preventing burnout along and creating a culture that encourages self-care. Training opportunities are essential to introduce multidisciplinary psychosocial trainees to pediatric oncology and assure an ongoing pipeline of individuals for the future.…”
Section: Discussionmentioning
confidence: 99%
“…“Burnout” first gained prominence in the 1970s when Herbert Freudenberger wrote about the loss of motivation and commitment to work that he and his colleagues experienced due to encountering excessive emotional and interpersonal workplace stressors (Freudenberger, 1974). Today there is concern about the level of burnout within health services since it is known to be associated with intention to leave the job/specialism, sickness absence, and presenteeism, as well as with patient dissatisfaction, medical error, and poor quality care (see, e.g., Argentero, Dell’Olivo, & Ferretti, 2008; Borritz et al, 2010; Demerouti, Le Blanc, Bakker, Schaufeli, & Hox, 2009; Estryn-Béhar et al, 2007; Poghosyan, Clarke, Finlayson, & Aiken, 2010; Shanafelt, 2010; Whitford, Nadel, & Fish, 2018). Systematic reviews of the literature have found that burnout is elevated in staff working in oncology services (Medisauskaite & Kamu, 2017; Trufelli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of using psychometrically sound measures of burnout has also been highlighted by those evaluating staff support interventions. A recent review of this evidence concluded that the lack of high-quality intervention studies, including studies that have used validated burnout measures, meant it was impossible to make recommendations on how best to prevent staff burnout (Whitford et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the issue is more complex than a simple equation of less time with patients equaling more burnout. My colleagues noted that, particularly in our field where the emotional stakes are so high, stressful time‐sensitive decisions can contribute to burnout, as can excessive clinical time . Clinical time is multiplicative instead of additive.…”
mentioning
confidence: 99%
“…My colleagues noted that, particularly in our field where the emotional stakes are so high, stressful time-sensitive decisions can contribute to burnout, as can excessive clinical time. 4 Clinical time is multiplicative instead of additive. Would that Friday have felt as challenging if it had been a Monday, without the stacked weight of four previous days?…”
mentioning
confidence: 99%